Piriformospora indica, a Cultivable Endophyte for Growth Promotion and Disease Management in Taro ( Colocasia esculenta (L.) - Lakshmipriya, P; Nath, Vishnu S; Veena, S S; Anith, K N; Sreekumar, J; Jeeva, M L (JOURNAL OF ROOT CROPS, 2017)
Taro leaf blight caused by Phytophthora colocasiae is the most destructive disease which causes about 50% yield loss. Use of resistant varieties, adopting cultural methods, application of fungicides and use of biological agents are the prevailing management practices against leaf blight. Piriformospora indica is an endophytic mycorrhiza like fungus which has shown pronounced growth promotional and disease suppressing activities in many crops. A study was conducted in ICAR- CTCRI, Sreekariyam to explore the potential of P. indica colonization in taro to promote growth and leaf blight resistance. The colonization ability of P. indica in taro varieties Sree Kiran and Muktakeshi was studied by Trypan blue staining, chitin specific WGA-AF 488 staining and also by amplifying species specific TEF1 gene. An increase in all the growth parameters was noted in the colonized plants compared to control plants in pot culture experiment. There was a substantial decrease in the disease incidence in colonized plants of both the varieties. During different stages of infection, about 57.6, 50.7 and 84.3% decrease in PDI was observed in P. indica colonized Sree Kiran and in case of Muktakeshi, reduction was 39.9, 56.2 and 72.5% over control. Increase in the activity of defense enzymes like chitinase, Î² -1, 3 glucanase and total phenol was observed in P. indica colonized plants compared to un-inoculated during initial hours of infection. Suppression Subtractive Hybridization was carried out to identify the differentially expressed genes in the colonized plants upon P. colocasiae infection. Various genes like Senescence associated genes, cytochrome P450, Delta (12) Oleic acid desaturase and calcium dependent protein kinase that take part in different defense related pathways were identified upon Blast2Go program. The study confirms that P. indica can be effectively utilized for growth promotion as well as an eco-friendly management strategy to combat taro leaf blight incidence.